Sesame Credit: Social Compliance Gamification in China - Alessandro Vieira dos Reis; Livia Topper Press (Journal of Games, Game Art, and Gamification, 2019)
Sesame Creditis the gamified Chinese social credit. It aims at monitoring and controlling the behavior of more than a billion citizens until 2020. Basing itself on the distribution of rewards and punishments to individuals, upon scoring based on the compliance of the aforementioned citizens towards laws and government interests. The present study probes Sesame Credit from data collected from academic papers, Chinese government official documents, as well as media articles.An interpretative analysis is conducted based on the Octalysismethod of gamification and the motivational method known as the Self-Determination Theory. Residing as main conclusions: a) the efficiency of the Sesame Credit depends on extensive and continual monitoring of the population by the Chinese government; b) despite the coercive aspects, such gamification is observed to be as popular in China, due to a millenary tradition of people’s compliance to the social and those of authority obedience